PROLEGOMENS TO METHODOLOGY OF RESEARCH OF HISTORY OF STUDY OPINION OF LITERATURE OF ANTIQUITY AND DARK AGES IN SPATIAL MEASURINGS THE «EAST - THE WEST» - Pylyp’yuk, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article metodolgiya study of poetics of ancient and medieval viewed through the action of the algorithm philosophical idea - aesthetic judgment - literary thought.